2021
DOI: 10.1186/s43046-021-00097-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of microRNA 17–92 cluster expression in Egyptian chronic lymphocytic leukemia patients

Abstract: Background Abnormal expression patterns of microRNAs (miRs) play an important role in the development and progression of malignancy. Identification of the clinical significance and prognostic value of these small molecules in chronic lymphocytic leukemia (CLL); a disease of heterogeneous biological landscape and clinical course, has always been of tremendous translational value. Aim To evaluate the prognostic value of microRNA17-92 cluster members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Similarly, Farzadfard et al reported higher circulating miR-19a-3p in CLL patients than in healthy subjects [ 2 ]. Moreover, Khalifa et al showed significant overexpression of all miR-17∼92 cluster members in CLL patients in comparison to the control group [ 34 ]. Several studies suggest that miR-19a-3p may play an important role in the pathogenesis and progression of CLL [ 2 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Farzadfard et al reported higher circulating miR-19a-3p in CLL patients than in healthy subjects [ 2 ]. Moreover, Khalifa et al showed significant overexpression of all miR-17∼92 cluster members in CLL patients in comparison to the control group [ 34 ]. Several studies suggest that miR-19a-3p may play an important role in the pathogenesis and progression of CLL [ 2 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, miR-18a was overexpressed in Egyptian patients with colonic polyps, PC, and CLL. [28][29][30][31] To the best of our knowledge, miR-18a did not correlate before to liver cirrhosis, and only its tumorigenic activity was known; however, the mechanism remains unclear. Murakmi et al proposed a panel of miRNAs to predict treatment response (IFNs) in chronic HCV infection and found that miR-18a was upregulated in the liver tissue of IFN non-responders.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Khalifa et al also found that miR-18a was overexpressed in patients with chronic lymphocytic leukemia compared to controls. 31 To the best of our knowledge, ours was the first study that evaluated the expression level of miR-18a in HCC.…”
Section: Introductionmentioning
confidence: 94%
“…In the same context, Lindberg et al elucidated that miRNA-17 was strongly upregulated in CD4+ T cells from the peripheral blood of multiple sclerosis (MS) patients (relapsing-remitting MS) and correlated with alterations in the expression of potential target genes potentiating its contribution to MS pathogenesis [ 41 ]. miRNA-17 was also overexpressed in the tissue and serum of several hematological and solid neoplasms, and its aberrant expression level was not only correlated with tumor progression and poor prognosis, but also mediated resistance to anti-cancer treatment [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Overall, it could be argued that miRNA-17 represents a promising diagnostic biomarker and therapeutic target in various neoplastic and immune disorders.…”
Section: Discussionmentioning
confidence: 99%